Coadministration of lopinavir/ritonavir and phenytoin results in two-way drug interaction through cytochrome P-450 induction - Lim, Michael L; Min, Sherene S; Eron, Joseph J; Bertz, Richard J; Robinson, Marjorie; Gaedigk, Andrea; Kashuba, Angela D M (Journal of acquired immune deficiency syndromes (1999), 2004)
Lopinavir/ritonavir (LPV/RTV) is a CYP3A4 inhibitor and substrate; it also may induce cytochrome P-450 (CYP) isozymes. Phenytoin (PHT) is a CYP3A4 inducer and CYP2C9/CYP2C19 substrate. This study quantified the pharmacokinetic (PK) drug interaction between LPV/RTV and PHT. Open-label, randomized, multiple-dose, PK study in healthy volunteers. Subjects in arm A (n = 12) received LPV/RTV 400/100 mg twice daily (BID) (days 1-10), followed by LPV/RTV 400/100 mg BID + PHT 300 mg once daily (QD) (days 11-22). Arm B (n = 12) received PHT 300 mg QD (days 1-11), followed by PHT 300 mg QD + LPV/RTV 400/100 mg BID (days 12-23). Plasma samples were collected on day 11 and day 22; PK parameters were compared by geometric mean ratio (GMR, day 22:day 11). P values <0.05 were considered significant. Following PHT addition, LPV area under the concentration-time curve (AUC0-12h) decreased from 70.9 +/-37.0 to 49.6 +/- 25.1 microg.h/mL (GMR 0.67, P = 0.011) and C0h decreased from 6.0 +/- 3.2 to 3.6 +/- 2.3 microg/mL (GMR 0.54, P = 0.001). Following LPV/RTV addition, PHT AUC0-24h decreased from 191.0+/-89.2 to 147.8+/-104.5 microg.h/mL (GMR 0.69, P = 0.009) and C0h decreased from 7.0+/-4.0 to 5.3+/-4.1 microg/mL (GMR 0.66, P = 0.033). Concomitant LPV/RTV and PHT use results in a 2-way drug interaction. Phenytoin appears to increase LPV clearance via CYP3A4 induction, which is not offset by the presence of low-dose RTV. LPV/RTV may increase PHT clearance via CYP2C9 induction. Management should be individualized to each patient; dosage or medication adjustments may be necessary.